Turning Points and Conflicting Interests: An Analysis of Changing Visions for Teaterhuset Avant Garden - Fieldseth, Melanie (Nordic Theatre Studies, 2022)
Teaterhuset Avant Garden (TAG) was a theatre in Trondheim that co-produced and presented the work of independent performing artists and groups from Norway and abroad. By taking a closer look at events between 1993 and 2003, this article situates TAG within broader aesthetic, organizational, and political contexts and analyses the impact of these events on visions for the theatre’s future. The article is based on archival research for a forthcoming book on TAG that deals with the period 1984–2018. In 2019, TAG changed its name to Rosendal Teater in honour of the historic building where it has since relocated.